Assessing Macrophyte and Ecosystem Service Changes in Shallow Eutrophic Coastal Waters Using Remote Sensing Methods - Johanna Schumacher; David Horn; Gabriela Escobar-Sánchez; Greta Markfort; Gerald Schernewski; Mario von Weber (Land)
Knowledge of the structure and spatial distribution of coastal water habitats is crucial for understanding coastal water systems. However, spatial habitat data are largely lacking, hampering ecological and ecosystem service assessments as required by EU policies. Mapping the structure, spatial distribution, and temporal dynamics of macrophytes is a particular challenge. In this study, we combined long-term macrophyte data with remote sensing methods (i.e., aerial and underwater drones, as well as SENTINEL-2 data) to assess their potential for spatial macrophyte monitoring and habitat-based ecosystem service assessments, in which ecosystem services were linked to habitats using the expert-based Baltic Ecosystem Service Potential Matrix. Greifswald Bay in the German Baltic Sea served as the case study for this research. Our aerial drone detected macrophytes up to a depth of 3 m that could be integrated into the existing macrophyte monitoring scheme of the Water Framework Directive. Reliable data from SENTINEL-2 were only obtained in optically shallow waters and could therefore only be used as proxy indicators to assess changes at a water body level. Despite the uncertainties and inaccuracies of the SENTINEL-2-based macrophyte maps, they were crucial for filling data gaps and enabled a spatially differentiated ecosystem service assessment for Greifswald Bay. However, we have shown that the commonly used matrix approach does not allow for the assessment of spatiotemporal changes at the water body level and is thus not suitable for supporting coastal and marine policy implementation.